Efektivitas Kombinasi Lumpur Aktif dan Natrium Bikarbonat (NaHCO3) dalam Pengelolaan Limbah Cair Industri Tebu (Saccharum officinarum L.) - Sanjaya, Refky; Subiantoro, Rijadi; Supriyatdi, Dedi (Jurnal Agro Industri Perkebunan, 2017)
In the sugarcane processing into sugar, it will produce g. About 52,9% of liquias, solid, and luquid waste. About 52,9% of liquid waste cause many problems. If the liquid waste directly discharged into the waters, it will cause pollution of water bodies, as well as air pollution around the river. The objective of this study is to obtain the effective and duration activity of the combination of active sludge and sodium bicarbonate in reducing the sugarcane industry of liquid waste. In this research, liquid waste management is done by aerobicized batch system stagnant in laboratory scale with the descriptive analysis. Biodegradation treatment is given to the liquid waste derived from anaerobic ponds in Bunga Mayang Sugar Mill, North Lampung. The treatment is L0 = without treatment (control), L1 = without sludge + 5 g.l-1 sodium bicarbonate, L2 = 100 ml.l-1 active sludge + 5 g.l-1 sodium bicarbonate. The result showed that application of 100 ml.l-1 active sludge + 5 g.l-1 sodium bicarbonate can increase the pH to 7,85, increase DO to 0,16 mg.l-1, reduce COD to 48,18%, increase sulfide content to 90,44%, increase turbidity to 95,4%, increase the wastewater temperature to 35oC, and the time required is shorter than the conventional anaerobic pools.   Keywords: active sludge, liqud waste, sodium bicarbonatePermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/650